2016
DOI: 10.1007/s00038-016-0842-8
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and economic burden of measles, mumps, pertussis, and varicella in Germany: a systematic review

Abstract: ObjectivesDespite the availability of vaccines and the existence of public vaccination recommendations, outbreaks of vaccine-preventable childhood diseases still cause public health debate. The objective of this systematic review was to provide an overview of the current epidemiology and economic burden of measles, mumps, pertussis, and varicella in Germany.MethodsWe systematically reviewed studies published since 2000. The literature search was conducted using PubMed and EMBASE. Also, we used German notificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 56 publications
0
15
0
1
Order By: Relevance
“…A recent literature review summarized the annual societal costs of varicella in the prevaccination era at 187.5 million euros, of which 18% were direct medical costs [46]. Hospitalizations due to (severe) varicella complications are the main contributors to the direct medical costs of varicella [47].…”
Section: Discussionmentioning
confidence: 99%
“…A recent literature review summarized the annual societal costs of varicella in the prevaccination era at 187.5 million euros, of which 18% were direct medical costs [46]. Hospitalizations due to (severe) varicella complications are the main contributors to the direct medical costs of varicella [47].…”
Section: Discussionmentioning
confidence: 99%
“…The disease remains a killer among vaccine-preventable diseases, especially among children of developing countries [34, 35]. Additionally, a recent systematic review of the epidemiologic and economic burden of measles, mumps, pertussis and varicella in Germany suggested that there was still considerable morbidity due to childhood diseases [36]. The present study estimation of a significant indirect cost associated with measles-related deaths may be a clear pointer that the disease continues to affect Somalia, especially among children 14 years and younger, robbing off their future productivity and contributions to society.…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic factors seemed to play a major role in vaccination compliance [17], while contracting measles has been itself associated with a significant economic burden [18].…”
Section: Epidemiology Of Measles and Mumps In Lebanonmentioning
confidence: 99%